Sexual dimorphism and determination of sex by morphometrics in Blue-fronted Amazons (Amazona aestiva) - Berkunsky, Igor (2009)
On current knowledge, it has not been possible to determine the sex of Blue-fronted Amazons (Amazona aestiva) in the hand, as males and females were thought not to differ in the colour of plumage or size. We used discriminant function analysis to develop equations for determining the sex of Blue-fronted Amazons using in-hand measurements. We took seven measurements of size and one measure of plumage colour (percentage of yellow on the head) from 202 birds in north-western Argentina. The sex of each individual was determined using DNA-based genetic techniques. For all size measurements, males averaged larger than females. Males also had a higher percentage of yellow plumage on the head than females. The percentage of yellow plumage (64%) and body mass (12%) had the highest degree of dimorphism, but also showed high within-sex coefficients of variation, correctly classifying 73% and 72% of the individuals respectively. Although bill-depth had a low degree of dimorphism (7%), it had the lowest coefficient of variation (4%) resulting in the most accurate single-measurement for sexing this species (80% of the individuals). A cross validation process revealed that a discriminant function including three measurements (bill-depth, tibial length and head-width) was more accurate and reliable for determination of sex than single measurements, classifying correctly85%of the individuals. Our results showthat Blue-fronted Amazons are sexually dimorphic for most characteristics of body size and show sexual dichromatism in the colour of the plumage of the head, which allows determination of sex of individuals by morphological variables that can be easily measured in the field.